Rancangan Sistem Rumah Pintar Type 45 Menggunakan Mikrokontroller ATMEGA328P Berbasis Aplikasi Android - Feri Prayogi Dahlan; Indra Roza (Universitas Harapan Medan, 2021)
Remote control is not something new, so the development of remote control has been done in many applications. The author designed automatic control of equipment and devices at home and buildings from a distance. The microcontroller used in this study was the ATmega 328P AVR type (Alf and Vegaard's Risc). ATmega 328P is an external microcontroller from atmel that has a RISC (Reduce Instruction Set Computer) architecture where each data execution process is faster than the CISC (Completed Intruction Set Computer) architecture. In the research, the application of access to devices in the home such as light control, fans and servo motors as a door driver using Arduino UNO as a microcontroller and Android applications as the main controller to control electronic devices. The circuit work system with a voltage of 3.3V to 5V, then each device in the circuit will be active (ArduinoUno, Bluetooth HC05 and Relay Module) with a 12V voltage on each tool. HC-05 As a connection with a maximum distance of 12M the tools can work. Based on the test results, it is obtained that the control system based on the android application using Arduino can be used as a controller for lights, fans and doors properly.